Vascular endothelial tissue factor contributes to trimethylamine N-oxide-enhanced arterial thrombosis. Issue 10 (5th August 2021) - Witkowski, Marco; Witkowski, Mario; Friebel, Julian; Buffa, Jennifer A; Li, Xinmin S; Wang, Zeneng; Sangwan, Naseer; Li, Lin; DiDonato, Joseph A; Tizian, Caroline; Haghikia, Arash; Kirchhofer, Daniel; et al.
Abstract: Aims: Gut microbiota and their generated metabolites impact the host vascular phenotype. The metaorganismal metabolite trimethylamine N-oxide (TMAO) is both associated with adverse clinical thromboembolic events, and enhances platelet responsiveness in subjects. The impact of TMAO on vascular Tissue Factor (TF) in vivo is unknown. Here, we explore whether TMAO-enhanced thrombosis potential extends beyond TMAO effects on platelets, and is linked to TF. We also further explore the links between gut microbiota and vascular endothelial TF expression in vivo . Methods and results: In initial exploratory clinical studies, we observed that among sequential stable subjects ( n  = 2989) on anti-platelet therapy undergoing elective diagnostic cardiovascular evaluation at a single-site referral centre, TMAO levels were associated with an increased incident (3 years) risk for major adverse cardiovascular events (MACE) (myocardial infarction, stroke, or death) [4th quartile (Q4) vs. Q1 adjusted hazard ratio (HR) 95% confidence interval (95% CI), 1.73 (1.25–2.38)]. Similar results were observed within subjects on aspirin mono-therapy during follow-up [adjusted HR (95% CI) 1.75 (1.25–2.44), n  = 2793]. Leveraging access to a second higher risk cohort with previously reported TMAO data and monitoring of anti-platelet medication use, we also observed a strong association between TMAO and incident (1 year) MACE risk in the multi-site Swiss Acute Coronary Syndromes Cohort, focusing on the subset ( n  = 1469) on chronic dual anti-platelet therapy during follow-up [adjusted HR (95% CI) 1.70 (1.08–2.69)]. These collective clinical data suggest that the thrombosis-associated effects of TMAO may be mediated by cells/factors that are not inhibited by anti-platelet therapy. To test this, we first observed in human microvascular endothelial cells that TMAO dose-dependently induced expression of TF and vascular cell adhesion molecule (VCAM)1. In mouse studies, we observed that TMAO-enhanced aortic TF and VCAM1 mRNA and protein expression, which upon immunolocalization studies, was shown to co-localize with vascular endothelial cells. Finally, in arterial injury mouse models, TMAO-dependent enhancement of in vivo TF expression and thrombogenicity were abrogated by either a TF-inhibitory antibody or a mechanism-based microbial choline TMA-lyase inhibitor (fluoromethylcholine). Conclusion: Endothelial TF contributes to TMAO-related arterial thrombosis potential, and can be specifically blocked by targeted non-lethal inhibition of gut microbial choline TMA-lyase. Graphical Abstract: